2021
DOI: 10.1093/eurjpc/zwab119
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the COVID-19 pandemic on in-hospital mortality in cardiovascular disease: a meta-analysis

Abstract: Aims  The COVID-19 pandemic has resulted in excess mortality due to both COVID-19 directly and other conditions, including cardiovascular (CV) disease. We aimed to explore the excess in-hospital mortality, unrelated to COVID-19 infection, across a range of CV diseases. Methods and results  A systematic search was performed for studies investigating in-hospital mortality among patients admitted with CV disease without SARS-CoV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
38
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 40 publications
(42 citation statements)
references
References 41 publications
3
38
1
Order By: Relevance
“…First, studies revealed a reduction in hospitalizations, procedures, and/or consultations for CVD in high [26][27][28][29][30], and low-and middle income countries (LMIC) [31,32], then an increase in out-ofhospital deaths [33,34]. Moreover, a rise in the proportion of in-hospital mortality for CVD was reported, being this effect larger where greater decline in admission rates occurred, suggesting hospitalizations of sicker patients or delivery of worse quality of care, corroborating our findings [35,36]. In parallel, other studies revealed that excess mortality in the pandemic period could not be explained exclusively by COVID-19 deaths, and excess CVD deaths was found in some countries, including Brazil, which is not surprising, knowing the beneficial effect of in-hospital timely treatment for the most lethal cardiovascular conditions, such as ACS [37][38][39].…”
Section: Discussionsupporting
confidence: 85%
“…First, studies revealed a reduction in hospitalizations, procedures, and/or consultations for CVD in high [26][27][28][29][30], and low-and middle income countries (LMIC) [31,32], then an increase in out-ofhospital deaths [33,34]. Moreover, a rise in the proportion of in-hospital mortality for CVD was reported, being this effect larger where greater decline in admission rates occurred, suggesting hospitalizations of sicker patients or delivery of worse quality of care, corroborating our findings [35,36]. In parallel, other studies revealed that excess mortality in the pandemic period could not be explained exclusively by COVID-19 deaths, and excess CVD deaths was found in some countries, including Brazil, which is not surprising, knowing the beneficial effect of in-hospital timely treatment for the most lethal cardiovascular conditions, such as ACS [37][38][39].…”
Section: Discussionsupporting
confidence: 85%
“…People who were sick at the time were more likely to be admitted to the trials where admission rates fell the most. 18 The aim of this review is to look at how the Corona virus has played a role in the development of several diseases that affect the heart and blood flow. Some of these diseases are myocardial damage, the effects of COVID-19 on people with congenital heart disease, heart failure, arrhythmias, microvascular angiopathy, and cardiac damage.…”
Section: Introductionmentioning
confidence: 99%
“…33,34 Moreover, a rise in the proportion of inhospital mortality for CVD was reported, being this effect larger where greater decline in admission rates occurred, suggesting hospitalizations of sicker patients or delivery of worse quality of care, corroborating our findings. 35,36 In parallel, other studies revealed that excess mortality in the pandemic period could not be explained exclusively by COVID-19 deaths, and excess CVD deaths was found in some countries, including Brazil, which is not surprising, knowing the beneficial effect of in-hospital timely treatment for the most lethal cardiovascular conditions, such as ACS. [37][38][39] However, even though the effect of the pandemics in CVD deaths had already been investigated in six Brazilian capital cities, the findings could not be extended to Belo Horizonte due to the heterogeneity of the pandemics in Brazil.…”
Section: Discussionmentioning
confidence: 95%